Low Cost Electrochemical Sensors for Silver, Chloride, Bromide and Iodide Ions - Pradhananga, Raja Ram; Rajbhandari Nyachhyon, Armila (Scientific World, 2010)
Low cost all solid state pressed pellet Ag+, halides and sulphide sensitive electrodes based on silver sulphide were fabricated. The electrodes have been tested and results compare favorably with commercial electrodes. Pure Ag2S electrode with internal silver metal contact was found to follow Nernstian equation from 1 x 10-1 to 1 x 10-5 M of silver ion with slope equal to 59.8 mV per decade change in concentration of Ag+ - ion. Electrodes fabricated from equimolar mixture of Ag2S and Ag - halide was found to be sensitive to the respective halide and silver ions. Iodide ion selective electrode prepared from a equimolar mixture of Ag2S and AgI was found to be selective to iodide ion with negligible interference from bromide and chloride ions. The potentiometric selectivity coefficient Kpot I,Br, Kpot I,Cl were found to be 1.77x10-2 and 7.94x10-3 respectively. All these electrodes were found to be selective to Ag+ ion with negligible interference with Kpot Ag, Hg equal to 1 x 10-5 Hg++ ion with selectivity coefficient. Keywords: Ion selective electrodes; Potentiometric selectivity coefficient; Silver sulphide. DOI: 10.3126/sw.v6i6.2631 Scientific World, Vol. 6, No. 6, July 2008 33-36